2018
DOI: 10.1186/s12893-018-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Continuous or interrupted suture technique for hepaticojejunostomy? A national survey

Abstract: BackgroundHepaticojejunostomy is commonly used in hepato-bilio-pancreatic surgery and a crucial step in many surgical procedures, including pancreaticoduodenectomy. The most frequently used techniques are the interrupted suture and the continuous suture technique. Currently, there is no data available in regard to the utilization of these techniques.MethodsIn total, 102 hospitals in Germany were invited between September and November 2017 to participate in this survey. Using a paper-based questionnaire, data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Fourth, the diameter of the bile duct in normal rats is about 1-2 mm, and can dilate to about 5 mm after 3 days of ligation, which can fully meet the needs of CJS. Fifth, CJS follows the clinical method of the continuous posterior wall and the intermittent anterior wall (27), and with practice, we can skillfully master the technique of CJS in rats. Finally, rats' metabolism is fast, the feeding cycle is short, and the scar formation of CJS can be observed 1 month after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the diameter of the bile duct in normal rats is about 1-2 mm, and can dilate to about 5 mm after 3 days of ligation, which can fully meet the needs of CJS. Fifth, CJS follows the clinical method of the continuous posterior wall and the intermittent anterior wall (27), and with practice, we can skillfully master the technique of CJS in rats. Finally, rats' metabolism is fast, the feeding cycle is short, and the scar formation of CJS can be observed 1 month after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…They also say that extended left hepatectomy is an independent risk factor for survival [21]. One of the most feared complications of hepaticojejunostomy is bile leakage (0.4-8%) [9,22,23]. Infection, ischemia, edema, applied techniques, and anastomotic tension in the bile ducts that are dissected are the most important causes of bile fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons prefer interrupted sutures in the anterior wall and continuous sutures in the posterior wall, and also some surgeons prefer interrupted sutures for the whole anastomosis. In a large survey study in Germany, it has been reported that both techni ques are equally pr eferable when performing hepaticojejunostomy, and there is no difference in complications [22]. We used an interrupted suture technique in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Manual hepaticojejunostomy is classically considered the preferred technique for reconnection of the biliary tree to the digestive tract. The adopted technique for this anastomosis mainly depends on the "surgical school" and expertise of the operating surgeon and can be performed with either continuous or interrupted sutures (2).…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications that can occur after hepaticojejunostomy are anastomotic leakage or dehiscence with biliary fistula and anastomotic stenosis. Biliary leakage is a short-term complication and can occur in 2.5-5% of cases (2), resulting in prolongation of hospital stay and need for further therapeutic procedures. Instead, anastomotic stricture, due to cicatricial stenosis or local recurrence in case of neoplastic disease is a late presenting complication, that manifests as jaundice, recurrent bile ducts lithiasis or cholangitis.…”
Section: Classically Hand-sewn Anastomosis Is Consideredmentioning
confidence: 99%